Avaliação de suportes hidrofóbicos aplicados à purificação de enzimas - Santos, Emanoela Fernanda Queiroz (Universidade Federal de São Carlos, 2019)
Enzymes are biological catalysts that present diverse applications, representing interesting perspectives for use in several branches of the industry: agribusiness, biofuels, and pharmacist. However, the recovery of broth enzymes is generally the most expensive step of a production process, as they are present in low concentration in a complex mixture of molecules. Thus, it is crucial to use appropriate (selective, efficient and inexpensive) purification processes to separate these high value-added biomolecules from complex extracts. The objective of this work was to verify the influence of the degree of hydrophobicity of different materials in hydrophobic adsorption processes, in order to characterize the enzyme-solid interaction besides to evaluate possibilities of application with main focus in the purification of biomolecules. The desorption process of the proteins was evaluated in a judicious manner by obtaining isotherms with the presence of TRITON-X-100 detergent. Initially, adsorbents constituted of silica matrices functionalized with carbon groups (C1 and C8) and octyl sepharose were tested on lipase adsorption of recombinant Bacillus thermocatenulatus (BTL-2) present in the centrifuged extract obtained after culturing and disruption of E. coli cells. The desorption isotherms, obtained in the presence of detergent, allow the evaluation of enzyme-solid interaction for the different substrates, making it possible to classify the degree of hydrophobicity of different hydrophobic supports applied to the purification of proteins. The results indicated higher enzyme-solid interaction for octyl sepharose, with greater selectivity in the adsorption process for lipase. This behavior of higher hydrophobic interaction later confirmed by high-purity lysozyme assays rather than the extract is probably due to the higher density of C8 (octyl) groups on the surface of octyl agarose with respect to C8 silica. Analysis of the results indicated that even with higher interaction, high desorption yields can be obtained for octyl agarose as a consequence of the large porosity of the particle and also of possible ionic interactions of the enzyme with the silica matrix. Thus, the particle porosity and nature of the adsorbent matrix are factors to be considered when analyzing desorption results to obtain higher protein elutriation. Despite the difficulty of desorption, the use of silica is still interesting, especially for applications of magnetic composites, due to its chemical stability and mechanical resistance. Thus, the work points out possible alternatives for the development of more efficient silica substrates for enzyme purification processes, such as higher particle porosity, higher silica matrix neutrality and preliminary tests with silica activated with less hydrophobic groups (diol ) resulting in high desorption yield of proteins, but with losses in the selectivity of the adsorption process.
Evaluation of hydrophic supports applied to enzyme purification
Keywords: Isotermas de dessorção; Hidrofobicidade de suportes; Purificação enzimática; Adsorção hidrofóbica; Lipases; Suportes de sílica; Octil-agarose; Desorption isotherms; Hydrophobicity of supports; Enzymatic purification; Hydrophobic adsorption; Silica supports; Octyl sepharose; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA